Immune modulation after traumatic brain injury - Bouras, Marwan; Asehnoune, Karim; Roquilly, Antoine (Frontiers in Medicine, 2022)
Traumatic brain injury (TBI) induces instant activation of innate immunity in brain tissue, followed by a systematization of the inflammatory response. The subsequent response, designed to limit an overwhelming systemic inflammatory response and to induce healing, involves the autonomic nervous system, hormonal systems, and the regulation of immune cells. This physiological response induces an immunosuppression and tolerance state that promotes to the occurrence of secondary infections. This review aims to describe the adaptive mechanisms following TBI, is focused on the immunological consequences of such traumas and develops innovative therapeutic approaches of immune modulation to restore homeostasis between the nervous system and innate immunity.